Location Approximation of a Wireless Device in a Wireless Local Area Network - Ho, Chiung Ching; Lee, Kian Chin (2008)
This paper describes a framework for approximating the location of wireless devices in an enclosed wireless computer network. Each wireless device's location is approximated using the location fingerprinting method. A test bed for the framework is described alongside a discussion on the results achieved, as well as validation of the achieved results. This paper is concluded with suggestions for practical implementation of location approximation for wireless devices as well as future research directions.